(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The positive effect of water swimming on the correction of scoliosis in children is noted due to the hydrodynamic pressure, which is evenly distributed over the body surface. This helps support the spine and reduce the load on muscles and joints, which is especially important in scoliosis. The purpose of the study: to theoretically substantiate the peculiarities of the use of swimming in improving the functional state of the musculoskeletal system in children 8-9 years old with scoliosis. Research methods. The work used the methods of the theoretical level of research: analysis, comparison, induction, deduction, systematization and generalization of scientific and methodical literature. Work results. Swimming used to correct scoliosis is a science-based rehabilitation method that uses the aquatic environment to improve physical fitness and reduce symptoms of musculoskeletal disorders. Aquatic exercises, in addition to their corrective functions achieved through a higher resistance environment, have a positive effect on increasing strength and endurance in children with scoliosis. Studies have shown that children who are engaged in swimming have achieved significantly better values of the functional state of the external breathing system, a decrease in the curvature of the scoliosis angle and spinal curves in the sagittal plane. Conclusions. Thus, swimming becomes an important tool in the rehabilitation of children with scoliosis, helping to solve physical problems and improve their general condition. This method is based on the principles of hydrodynamic pressure and contributes to the comprehensive physical development of children, increasing their quality of life and the functional state of the musculoskeletal system.